Descriptive and rapid sensory profiling of wheat and wheat-sorghum biscuits fortified with longhorn grasshopper (Ruspolia differens) powder - Amos Kipkemoi Ronoh; Charlotte Atsango Serrem; Susan Balaba Tumwebaze; Gertrude Mercy Were (Applied Food Research)
Protein Energy Malnutrition is a public health challenge that negatively affects young children in developing countries. Formulation of foods fortified with edible insects is a potentially sustainable approach to increase the protein quality in the diet of young children. Biscuits are a suitable fortification vehicle as they are popular among young children and have an extended shelf life. The aim of this study was to evaluate the effect of fortifying wheat and wheat-sorghum flours with Ruspolia differens powder (RDP) on sensory characteristics and acceptability of biscuits. Ten biscuit formulations were made by replacing part wheat and wheat-sorghum flours with 5, 15, 25, and 40 % RDP. Sensory evaluation was conducted using a descriptive panel to characterize the ten biscuit formulations, a Check-All-That-Apply questionnaire, and intent to buy. Principal component analysis for 38 attributes for biscuits scored by a descriptive sensory panel revealed that the first two principal components explained 82 % of the total variation where principal component 1 accounted for 60 % due to the cereal component, while 22 % (principal component 2) was due to concentration of grasshopper powder. Cluster analysis identified three distinct groups of consumers with similar biscuit preferences. The drivers of liking and intent to purchase biscuits are wheat based, with vanilla aroma and flavor, sweet flavor and baked biscuit aroma with a light colour. Compositing the biscuits with RDP imparts positive consumer attributes of crunchy texture and baked aroma. These protein rich biscuits have the potential to be used as a supplementary food because of the positive consumer attributes.